1988
DOI: 10.1152/ajpendo.1988.255.6.e886
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral metabolism of PTH: fate of biologically active amino terminus in vivo

Abstract: Clearance of intact parathyroid hormone (PTH) from blood is associated with rapid uptake by liver and kidney, limited proteolysis by tissue endopeptidases and, within minutes, appearance of circulating carboxyl-(COOH)-terminal PTH fragments. The fate of the corresponding amino(NH2)-terminal portion of the hormone during this peripheral metabolism is still unknown, however. To determine this, we have employed [35S]bovine PTH (bPTH) labeled to high specific activity at NH2-terminal methionines, which permits dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…The difference from prior results is probably best explained by the fact that the hPTH(1-84) preparation used here was biologically active while the 125 I-bPTH(1-84) used previously was not (9, 10, 29, 30) because of chloramine-T iodination. Prior studies have demonstrated a slightly different tissue distribution (more in the liver, less in the kidneys) of bioactive 125 I-bPTH(1-84) (31) and of bioactive internally labeled bPTH(1-84) with a somehow shorter half-life (32). Finally, more PTH fragments were observed in NPX rats at all time points, reflecting the absence of kidney clearance and increased production in the presence of more available substrate.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The difference from prior results is probably best explained by the fact that the hPTH(1-84) preparation used here was biologically active while the 125 I-bPTH(1-84) used previously was not (9, 10, 29, 30) because of chloramine-T iodination. Prior studies have demonstrated a slightly different tissue distribution (more in the liver, less in the kidneys) of bioactive 125 I-bPTH(1-84) (31) and of bioactive internally labeled bPTH(1-84) with a somehow shorter half-life (32). Finally, more PTH fragments were observed in NPX rats at all time points, reflecting the absence of kidney clearance and increased production in the presence of more available substrate.…”
Section: Discussionmentioning
confidence: 87%
“…In the first case, gel chromatography was used and was probably unable to separate these large 125 I-PTH fragments from 125 IbPTH(1-84), and/or 125 I-PTH fragments were not sequenced long enough to identify 125 I-non(1-84) PTH (9,10,29). In the second case (32), HPLC was performed on gel chromatography fractions and not on untouched samples, leading to the same conclusion.…”
Section: Discussionmentioning
confidence: 93%
“…PTH(1-84) and its various fragments are eliminated by the liver and by glomerular filtration in the kidneys (1)(2)(3)(4)(5). In patients with impaired renal function, plasma clearance of PTH and other PTH fragments is diminished.…”
Section: Parathyroid Hormone Is An 84 -Amino Acid Polypeptide [Pth(1-mentioning
confidence: 99%
“…This event generates a series of N-truncated "CPTH" fragments (the corresponding N-terminal segments are destroyed in situ) that reenter the circulation and are cleared mainly by glomerular filtration, an important route for PTH clearance as well (4 ). Chemical analysis of PTH fragments isolated from rat blood after administration of radiolabeled bovine PTH established that hepatic metabolism yields a family of CPTH fragments with NH 2 termini ranging between residues 34 and 43, although the methods used likely would not have detected substantially larger CPTH fragments (5 ). Interestingly, chemically similar CPTH fragments are secreted directly from the parathyroid glands as well, and the ratio of secreted CPTH fragments to intact PTH increases as blood calcium increases (6,7 ).…”
mentioning
confidence: 99%